The Role of Socio-Culture and the Factors Affecting the Development of the Baduy Community - Sumawijaya; I Nyoman Sumaryadi; Erliana Hasan; Sampara Lukman (GoAcademica Research & Publishing, 2020)
The Baduy tribe is one of the tribes located in Lebak Regency, Banten Province. The Baduy tribe firmly adhere to the customs and culture of their ancestors. The Baduy tribe is very closed because they carry out the mandate outlined by their ancestors, namely in the form of a simple lifestyle, away from modern cultural influences and presenting themselves in the way of life carried out by their ancestors without changing it. The consequence of this makes the Baduy tribe very little touched by the progress and rapid development. This study aims to analyze the socio-cultural role in improving the development of the Baduy people and the factors that support and hinder the Baduy community's development. This study used a qualitative approach, using descriptive methods to analyze the collected data. The results showed that association with the outside world made the Baduy people come into contact with modern technology, which for hundreds of years so that many social changes occurred in the Baduy community. The research also found factors that encourage and hinder the development of the Baduy community, including contact with other cultures, open community systems, community dissatisfaction, lack of relationships with other communities, late development of knowledge, and entrenched customs.